A Documentary History of Art, Volume 2 Michelangelo and the Mannerists, The Baroque and the Eighteenth Century - Holt, Elizabeth Gilmore (Princeton University Press, 2022)
The theory and practice of art underwent a number of fascinating changes between the sixteenth and the eighteenth centuries, changes which are clearly revealed in this unique collection of letters, journals, essays, and other writings by the artists and their contemporaries. In the poems of Michelangelo, the Dialogues of Carducho, or the Discourses of Sir Joshua Reynolds, one discovers the stylistic and philosophical concerns of the artist, while the record of Veronese's trial before the Holy Tribunal, the diary of Bernini's journey in France, the letters of Rubens and Poussin or biographical sketches of Rembrandt and Watteau reveal not only the personalities but also the conditions of the times.These basic and illuminating documents, now again available in paperback, provide an unparalleled opportunity for insight into the art and ideas of the periods the author discusses